A compelling need to empirically validate bipolar depression - Martino, Diego Javier (2023)
We read with great interest the paper by Ghaemi et al. (2022) entitled “Clinical research diagnostic criteria for bipolar illness (CRDC-BP): rationale and validity” recently published in the International Journal of Bipolar Disorders. Essentially the authors highlight the need for “new, purely research-based diagnostic criteria aimed primarily at validity” as “essential to the success of biological and pharmacological research”. Tus, they propose a series of diagnostic criteria marking a counterpoint to the Research Diagnostic Criteria in 1978, the immediate antecedent of DSM-III (1980), which focused on improving reliability rather than validity. We welcome that a group of prominent researchers emphasize the need for valid diagnoses based on empirical data as a primary condition for advancing our knowledge on bipolar disorder (BD). However, we would like to contribute with an additional perspective regarding the current clinical construct of bipolar depression...